Risk of venous thromboembolism in rheumatoid arthritis, and its association with disease activity: a nationwide cohort study from Sweden. Issue 2 (8th October 2020) - Molander, Viktor; Bower, Hannah; Frisell, Thomas; Askling, Johan
Abstract : Objective: To assess the incidence of venous thromboembolism (VTE) in rheumatoid arthritis (RA) relative to individuals without RA, and to investigate the relationship between aspects of clinical disease activity in RA and the risk of VTE. Methods: We conducted a nationwide register-based cohort study 2006 through 2018 using the Swedish Rheumatology Quality Register linked to other national patient registers to identify all patients with RA with at least one registered rheumatologist visit during the study period (n=46 316 patients, 322 601 visits). The Disease Activity Score 28 erythrocyte sedimentation rate (ESR) (DAS28 ESR) and its components served as the exposure, and a VTE event within the year following the visit was the main outcome. We also included general population referents (1:5) matched on age, sex and residential area. Results: Based on 2241 incident VTE events within 1 year of each included visit, and 5301 VTE events in the general population cohort, the risk ratio for VTE in RA was 1.88 (95% CI 1.65 to 2.15). Among patients with RA, the risk (and risk ratio) increased with increasing RA disease activity, from 0.52% following visits in remission to 1.08% following visits with DAS28 ESR high disease activity, RR compared with remission=2.03, 95% CI 1.73 to 2.38. Compared with the general population, also patients with RA in DAS28 ESR remission were at elevated VTE risk. Conclusions: This study demonstrates a strong association between clinical RA disease activity measured by DAS28 ESR and the risk of VTE. RA disease activity can be used as an additional tool for VTE risk stratification in patients with RA.